Cellular adenylate energy charge and adenine nucleotides in brain tissue during hypoglycemia in newly born BALB/c mice pups - Hassib Narchi; Priyadharshini Yuvaraju; Junu A. George; Richard L. Jayaraj; Radhakrishnan Subramanian (Open Exploration Publishing Inc., 2024)
Aim: Hypoglycemia occurs in the neonatal period but the exact pathophysiology of the resulting brain injury at the cellular level is not well known. Therefore, a neonatal murine model was developed with insulin-induced hypoglycemia, to analyze the in-vitro effects of hypoglycemia on brain nucleotides and adenylate energy charge (AEC) throughout the first ten days of life. Methods: Newly born BALB/c pups between one and ten days of age were used. In each age group, six pups were subjected to insulin-induced hypoglycemia and six others served as controls. In both groups, immediately after euthanasia, brain tissues were collected. The in-vitro effects of hypoglycemia on brain nucleotides [adenosine monophosphate (AMP), adenosine diphosphate (ADP), and adenosine triphosphate (ATP)] were analyzed using liquid chromatography with tandem mass spectrometry (LC-MS/MS) as well on AEC. Results: In the controls, the cellular AEC steadily decreased with age by at least 50% over the 10-day study period (P < 0.05) except in the parietal tissue (P = 0.30) where it remained stable throughout that period. The most marked decrease was observed in the occipital tissue (P < 0.001). In the hypoglycemic mice, AEC in both the parietal and occipital tissues decreased significantly more than in the controls, more rapidly and pronounced between day 2 and 5 in the occipital tissue, reaching very low levels from day 5 onward. Except in the occipital tissue, none of the adenine nucleotides on its own, including ATP, reflected the cellular AEC. Conclusions: Over the first ten days of life, hypoglycemia progressively depleted cellular AEC in the brain, unlike cellular ATP concentration which did not appropriately reflect cellular energy.